Antimicrobial Potential of Panchagavya Formulation from Indian Cow Breeds - Rai, Satyam; Rao, Priyanka Singh; Sharma, Vivek; Pradhan, Diwas; Singh, Richa (International Journal of Bio-resource and Stress Management, 2022)
The Sanskrit word panchagavya means the “mixture of five cow products”, viz. dung, urine, milk, curd and ghee. The present study involves standardization of method for preparation of panchagavya formulations on the basis of antimicrobial activity. For that, panchagavya prepared in three different ratios (A, B and C) were kept for fermentation at two different temperatures (37° and 25°C) up to 30 days. At 10 days interval, raw samples and their distillates were analyzed for pH and antimicrobial activities against selected indicator strains. The ratio A, B and C had pH value 7.49±0.09, 8.01±0.16 and 8.23±0.26, respectively at 0 day while distillate of corresponding samples showed pH towards the alkaline side. On fermentation the pH value of RA and its distillate shifted towards acidic side while that of ratio B and C and their distillate towards alkaline side. No antibacterial activity was observed against gram negative bacteria. The distillate of ratio A (DRA) fermented at 37°C showed maximum activity against the two-gram positive bacteria i.e.,Bacillus. subtilis and Bacillus. cereus on 20th day. Similarly in antifungal activity, the distillate of ratio A (DRA) fermented at 37°C showed maximum activity against Candida. Butyri, Rhodotorulaglutinis, Penicillium camemberti and Aspergillus niger. Overall, the highest antimicrobial activity was observed in the distillate of panchagavya prepared by mixing all the raw ingredients in equal ratio, fermented at 37°C up to 20 days. The activity was more predominant in panchagavya distillate of Gir and Sahiwal compared to Tharparkar and Karan Fries.